Ectopic Bone Tissue Engineering in Mice Using Human Gingiva or Bone Marrow-Derived Stromal/Progenitor Cells in Scaffold-Hydrogel Constructs - Shanbhag, Siddharth; Kampleitner, Carina; Mohamed-Ahmed, Samih; Yassin, Mohammed Ahmad; Dongre, Harsh; Costea, Daniela Elena; Tangl, Stefan; Hassan, Mohamad Nageeb; Stavropoulos, Andreas; Bolstad, Anne Isine; Suliman, Salwa; Mustafa, Kamal (Frontiers in Bioengineering and Biotechnology, 2021)
Three-dimensional (3D) spheroid culture can promote the osteogenic differentiation and bone regeneration capacity of mesenchymal stromal cells (MSC). Gingiva-derived progenitor cells (GPC) represent a less invasive alternative to bone marrow MSC (BMSC) for clinical applications. The aim of this study was to test the in vivo bone forming potential of human GPC and BMSC cultured as 3D spheroids or dissociated cells (2D). 2D and 3D cells encapsulated in constructs of human platelet lysate hydrogels (HPLG) and 3D-printed poly (L-lactide-co-trimethylene carbonate) scaffolds (HPLG-PLATMC) were implanted subcutaneously in nude mice; cell-free HPLG-PLATMC constructs served as a control. Mineralization was assessed using micro-computed tomography (µCT), histology, scanning electron microscopy (SEM) and in situ hybridization (ISH). After 4–8 weeks, µCT revealed greater mineralization in 3D-BMSC vs. 2D-BMSC and 3D-GPC (p < 0.05), and a similar trend in 2D-GPC vs. 2D-BMSC (p > 0.05). After 8 weeks, greater mineralization was observed in cell-free constructs vs. all 2D- and 3D-cell groups (p < 0.05). Histology and SEM revealed an irregular but similar mineralization pattern in all groups. ISH revealed similar numbers of 2D and 3D BMSC/GPC within and/or surrounding the mineralized areas. In summary, spheroid culture promoted ectopic mineralization in constructs of BMSC, while constructs of dissociated GPC and BMSC performed similarly. The combination of HPLG and PLATMC represents a promising scaffold for bone tissue engineering applications.